2021
DOI: 10.1088/1361-6560/abe554
|View full text |Cite
|
Sign up to set email alerts
|

Al2O3:C optically stimulated luminescence dosimeters (OSLDs) for ultra-high dose rate proton dosimetry

Abstract: The response of Al2O3:C optically stimulated luminescence detectors (OSLDs) was investigated in a 250 MeV pencil proton beam. The OSLD response was mapped for a wide range of average dose rates up to 9000 Gy s−1, corresponding to a ∼150 kGy s−1 instantaneous dose rate in each pulse. Two setups for ultra-high dose rate (FLASH) experiments are presented, which enable OSLDs or biological samples to be irradiated in either water-filled vials or cylinders. The OSLDs were found to be dose rate independent for all do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 36 publications
0
30
0
Order By: Relevance
“…3 does not necessarily exclude dose-linearity over a wider dose range. Previous studies have demonstrated OSL response to be dose-rate independent in :C 32 , 33 , but any dose-rate dependence in LYSO:Ce is subject to further investigation.…”
Section: Discussionmentioning
confidence: 93%
“…3 does not necessarily exclude dose-linearity over a wider dose range. Previous studies have demonstrated OSL response to be dose-rate independent in :C 32 , 33 , but any dose-rate dependence in LYSO:Ce is subject to further investigation.…”
Section: Discussionmentioning
confidence: 93%
“…The saturating exponential in Eq. ( 1 a) was fitted to the OSLD response as a function of the dose measured with the ionization chamber in line with previous works 13 .…”
Section: Methodsmentioning
confidence: 97%
“…The optically stimulated luminescence (OSL) of allows the estimation of both dose and LET, but with the advantage of only requiring a single detector, and has been demonstrated 13 to be dose-rate independent in proton beams up to .…”
Section: Introductionmentioning
confidence: 99%
“…Even for a FLASH dose rate of 1000 Gy/s, the dose per pulse is of the order of 10 μGy. Also in terms of ion recombination, the dose delivery can be considered continuous 19 …”
Section: Methodsmentioning
confidence: 99%